Miejsce i rola Starego Testamentu w adhortacji Benedykta XVI Verbum Domini (na przykładzie stosowanych cytacji) - Nawrot, Janusz (Poznańskie Studia Teologiczne, 2012)
Benedict XVI underscores the unchanging validity of the Old Testament. In the exhortation Verbum Domini this is manifested by quotations of texts from the Hebrew Bible or the Septuagint in the context of problems discussed in connection with the theology of any of the New Testament writings. Moreover, the Pope shows Jesus himself as a new perspective of what is foretold by the text of the First Covenant and that is why the Old Testament becomes a lasting point of reference for the conduct of contemporary believers. It is also a unique and uniform source of revelation of the word for the Church. The Pope’s exegesis of the texts is decidedly more theological than literal so it is worthwhile to undertake the analysis of particular quotations in a broader perspective of biblical theology and the entire teaching of the Church. The exhortation sincerely recommends such a task.